Heavily Indebted Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Status of Implementation. (Policy Papers; Policy Paper, 2010)
This report provides an update on the status of implementation, impact, and costs of the Heavily Indebted Poor Country (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI). Debt relief provided under the Initiatives has substantially alleviated debt burdens in recipient countries. Through the continued use by IDA and the Fund of the flexibility available in the framework governing the HIPC Initiative and the MDRI, significant progress has been achieved under the Initiatives since the last report.